Clinical and radiographic findings without the use of bone substitute materials in extraction sockets and delayed implant placement- A case series - Lanka Mahesh; Jose Luis Calvo Guirado; Sagrika Shukla; Varun Raj Kumar; Yuvika Raj Kumar (Elsevier, 2020)
Aim: To observe clinically and radiographically (CBCT), the extent of bone resorption in extraction socket without the use of bone graft substitutes and delayed implant placement. Material and methods: 50 compliant patients were selected for study. All the patients who were advised extraction were followed up for entire duration of the treatment, at 5th week CBCT showed horizontal and vertical bone loss. To prevent further bone resorption, after 5 weeks implant was placed along with bone graft. Results: Bone resorption after extraction is an unavoidable phenomenon. Clinical and radiographic (CBCT) analysis showed massive bone resorption by 5th week. At 5 month CBCT, all patients showed stable implant integration. There was no implant failure at the end of the study. Conclusion: Alveolar preservation is proven to slow down socket wall collapse with the use of a bone substitute material without which larger procedures maybe needed to restore alveolar integrity and harmony. Immediate implant placement is effective when bone graft is placed in the jumping distance.